2011
DOI: 10.1242/jeb.045351
|View full text |Cite
|
Sign up to set email alerts
|

Elastic deformation and energy loss of flapping fly wings

Abstract: SUMMARY During flight, the wings of many insects undergo considerable shape changes in spanwise and chordwise directions. We determined the origin of spanwise wing deformation by combining measurements on segmental wing stiffness of the blowfly Calliphora vicina in the ventral and dorsal directions with numerical modelling of instantaneous aerodynamic and inertial forces within the stroke cycle using a two-dimensional unsteady blade elementary approach. We completed this approach by an experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 62 publications
3
81
0
Order By: Relevance
“…The Reynolds number for species such as hummingbirds is Re ¼ O(10 4 ), while for smaller insects, such as fruit flies or honeybees, Re ¼ O(10 2 2 10 3 ). These small insect flyers have flexible wings that experience large deformations just like birds and bats [11,12]. It has been, for example, shown that wing deformations [13,14] can enhance the force generation and efficiency of a locust operating at Re % 4 Â 10 3 [13], or a hawkmoth at Re % 6.3 Â 10 3 [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Reynolds number for species such as hummingbirds is Re ¼ O(10 4 ), while for smaller insects, such as fruit flies or honeybees, Re ¼ O(10 2 2 10 3 ). These small insect flyers have flexible wings that experience large deformations just like birds and bats [11,12]. It has been, for example, shown that wing deformations [13,14] can enhance the force generation and efficiency of a locust operating at Re % 4 Â 10 3 [13], or a hawkmoth at Re % 6.3 Â 10 3 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, tethered flying Drosophila actively control left/right wing rotation timing to initiate yaw turns [20]. However, hovering fruit flies [21] and honeybees [22], beetles [11] and hymenopterans in general exhibit symmetric rotation [11], which means that they rotate their wings around the same time as they reverse the stroke.…”
Section: Introductionmentioning
confidence: 99%
“…[97] While all patterns tend to promote an exponential decay in bending stiffness from wing base to tip, spatial mapping of veins plays an important role in flexibility variation between the leading and trailing edges of wings ( Figure 6). [98,99] As a method to promote further deformations within this relatively rigid venous structure, the cuticle of certain insect wings contains flexible linear segments, which act as fold lines. [100] Such bands are distributed independently of support veins-those running radially (base to tip) mediate bending and twisting, while others oriented transversely (leading edge to trailing edge) act as one-way hinges to help the wings bend and reset after the completion of a downstroke.…”
Section: Insect Wing Morphology and Compositionmentioning
confidence: 99%
“…Firstly, the energetic cost consumed by hovering insect only considers the time-averaged positive mechanical power output used to overcome aerodynamic damping and inertial power [54][55][56]. Secondly, the elastic storage can be recovered completely and thus be treated as a part of the negative power of the system [55][56][57]. Thirdly, the wing motions are powered by actuators located at the wing shoulder.…”
Section: Power Density Modelmentioning
confidence: 99%
“…Here, the optimal values for non-dimensional location of the pitch axis, which consistently approach the leading edge for the optimization involving WGP (Table 3), is only the numerical solution but not reflect the real situation since the pitch axis might be not a straight line. In engineering design, the location of pitch axis needs to be determined by experimentally measuring the optimal angle of attack [57]. In order to survive in a complex environment such as predation or evading maneuverability with limited energy, fruit fly might evolve to have pony-size WGP adaptive to its body size in millimeter scale but high flapping frequency and large flapping amplitude under the strategy of minimum power consumption.…”
Section: Sensitivity Analysis For Combined Optimal Wgp and Wkpmentioning
confidence: 99%